Administration of selenomethionine in combination with serine benefits diabetes via gut microbiota - Cui, Xiaoyan; Chen, Jingqing; Yang, Yuexi (Frontiers in Microbiology, 2022)
Either selenium or serine could modulate glucose homeostasis, however, whether there are synergistic effects of selenium with serine on diabetes remains to be unknown. In the present study, eight male db/m mice were used as a control, and twenty-four male diabetic db/db mice were either orally gavaged with PBS, or with selenomethionine alone, or with both selenomethionine and serine, to investigate the effects of selenomethionine and serine on body weight and glucose level. Furthermore, intestinal microbiota composition was analyzed and fecal microbiota transplantation (FMT) was performed to explore whether microbes mediate the beneficial effects of selenomethionine and serine. The results showed that administration of selenomethionine decreased body weight, adipose tissue weight and serum glucose level in db/db diabetic mice. Importantly, administration of selenomethionine in combination with serine exerted better effects than selenomethionine alone did. Furthermore, a combined administration of selenomethionine and serine restored the microbial composition in diabetic mice. Corynebacterium glutamicum, Bifidobacterium pseudolongum and Aerococcus urinaeequi were significantly decreased, whereas Lactobacillus murinus was increased in mice in the selenomethionine group and selenomethionine in combination with serine group, when compared with those in the db/db group. FMT decreased body weight and glucose level in db/db mice, further indicating that microbes play critical roles in the beneficial effects of selenomethionine and serine. Thus, we concluded that administration of selenomethionine in combination with serine benefits diabetes via gut microbes. Our results suggested that the synergic application of selenomethionine and serine could be potentially used for the treatment of diabetes.